Pengaruh Price Discount dan Shopping Lifestyle Terhadap Impulse Buying Konsumen Hypermart Malang Town Square Kota Malang - Lailil Badriyah, Isnaini; Boedhi Santoso, Eko (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Price discounts can increase the value of impulsive purchases of a product. Apart from price discounts, companies also need to consider things that can be of concern to consumers in their lifestyle shopping habits, namely paying attention to the quality of the products sold, both ensuring product contents and product packaging. This research is quantitative research with price discount, shopping lifestyle and impulse buying variables. Purposive sampling was used as a data collection method using a questionnaire, and the number of respondents selected was 100 people. The results of this research explain that price discounts and shopping lifestyle have a partial or simultaneous effect on the impulse buying of Hypermart Malang Town Square consumers, Malang City. Hypermart Malang Town Square is expected to maintain an attractive promotional strategy related to discount information provided to consumers so that consumers know and are interested in shopping and can maintain the daily products that consumers need, so that shopping lifestyle can increase consumer impulse buying.